Giant Arachnoid Cyst of Interhemispheric Fissure with Bilateral Extension across Midline Presenting with Seizure after Motor Vehicle Accident: A Serious Acute Post-Traumatic Complications and Management Review - Guru Dutta Satyarthee (Open Journal of Trauma - Peertechz Publications, 2017)
Intracranial arachnoid cyst (IHAC) is considered as rare congenital lesions. Usually the arachnoid cyst remains asymptomatic and incidentally picked -up on routine cranial imaging. Mostly, the intracranial  arachnoid cyst is located in the sylvan fissure, cerebello-pontine angle, or suprasellar region. However, arachnoid cyst located in the interhemispheric fi ssure is regarded as extremely uncommon, however  observed only in children due to clinical symptoms, however, extremely rare in adult. Till date only fifteen such cases are reported in the western literature. Most of reported cysts were associated with extension from interhemispheric fissure to either one side across the midline. To the best of author's knowledge,  current case is unique and represent fi rst case of giant IHAC in the western literature, with gigantic size associated with extension across the midline bilaterally and occurring in a relatively younger age and  presenting with seizure, occurred two hours following trauma, also necessitated cystoperitoneal shunt surgery for associated raised intracranial pressure and noticed headache relief and control of seizure on antiepileptic medication noticed in the follow-up period.